Cell Sizes Study of Encapsulated Coconut Oil for Heat Exchanger Application. Issue 1 (February 2021) - Jurizat, Aldissain; Andoni, Heri; Sutjahja, Inge Magdalena; Wonorahardjo, Surjamanto
Abstract: Study of heat exchanger system using phase change material (PCM) for air conditioning system application in buildings is still very rare. The potential application of natural materials such as coconut oil as heat storage and heat exchangers in buildings in the tropics is quite large because the melting point of this material is in the human comfortable temperature range and a relatively large heat enthalpy corresponds to the stored heat. The heat exchange of such materials is strongly influenced by its thermal conductivity so that the heat flow rate greatly affects the effectiveness of heat exchange. This paper shows the role of cell size on the effectiveness of coconut oil as the heat exchanger. The experiment was conducted by measuring the temperature of coconut oil cell with diameter 4 cm, 5 cm, 6 cm, 8 cm, 12 cm and 16 cm in the natural air environment. The temperature was measured using thermocouples for 2 × 24 hours with a data retrieval interval for 15 minutes. The results showed that cell size provides different responses to changes in environmental temperature, so that its role as a heat exchanger can be designed according to its needs.